Aspects of Slavic linguistics : formal grammar, lexicon and communication - Mueller-Reichau, Olav; Guhl, Marcel (Language, Context and Cognition, 2017)
Human languages are economical systems of knowledge, which usually contribute to the formation and interpretation of utterances only what cannot be supplied by other conceptual systems. Language, Context and Cognition explores conceptual underspecification and context-dependence in grammar and text-production as essential properties of natural languages. This requires close cooperation of linguistics with cognitive science, logic and pragmatics.